Organizing Committee: QAI 2025 (2025 IEEE International Conference on Quantum Artificial Intelligence (QAI), 2025)
Background We compared the performance of self-reports, pill counts, and electronic adherence measures in monitoring antiretroviral therapy (ART) adherence and association with viral suppression among adolescents living with HIV (ALHIV). Setting This study was conducted among 39 study clinics in the Greater Masaka region in Southern Uganda. Methods We used baseline data from 702 ALHIV aged 10-16 years receiving ART. Self-report was assessed using a three-item tool and pill counts were unannounced, while Wisepill captured device openings over 30 days. We determined the sensitivity, specificity, and area under the receiver-operator characteristic (ROC) curve for each adherence measure in discriminating ALHIV based on their viral suppression (<200 copies/mL) status. We also fit multilevel logistic regression models to determine the association between each adherence measure and viral suppression. Results On average, 73% of ALHIV reported good (≥90%) ART adherence, while 67.1% of ALHIV achieved viral suppression. We found disagreement between adherence measures, with agreement coefficient ranging between 0.410 (self-report vs. Wisepill) and 0.545 for pill counts vs. Wisepill. All 3 adherence measures had low ability to predict viral suppression, with AUCs ranging between 0.560 for pill counts and 0.616 for self-reported adherence. Only self-reported adherence had a significant relationship with viral suppression, with OR = 2.16 (95% CI: 1.25 to 3.81) and P = 0.006. Conclusions Substantial discrepancies exist across adherence measures. In this setting, low self-reported adherence can help in identifying adolescents at risk of virologic failure, although high self-reported adherence does not reliably exclude viremia.